Perhitungan Soda Ash untuk Menetralkan Air Asam Tambang Pada Penambangan Bijih Timah di Area Nibung PT Kobatin, Provinsi Bangka Belitung - Shenny Linggasari; Hasywir Thaib Siri; Nessy Salsabilita (Retii, 2018)
ABSTRACTNibung area is one of the tin mining location in PT. Koba Tin which located at Nibung Village, Koba District, Bangka Belitung Province. In this area, there are three pits. They are Merbuk, Kenari, and Pungguk. Pungguk is the active pit which still doing the activity of mine, while the other pits had been completed (mined out). Mining process resulted sulfida minerals which located in layer of tin grow up. There is oxidation of air and water in pit, which sulfida minerals located and then acid rock mine. The other reason which acid rock drainage located , because primary rock of tin is Granit rock. Granit is one of the acid rock. pH of acid water in the location is 3,51. According to Minister of Environment Regulation No. 4 of 2006 on the Standards of Quality Tin Ore Mining Waste water , pH water which is out from the mine activity has 6-9. So, PT. Koba Tin should have technical review of water treatment that can raise the pH of the exit to the public waters (rivers). PT. Koba Tin used A chemical material, soda ash (Na2CO3) . The result of my research, to raise the pH of the water according to the rules, with inlet pH 3,4 become 6,5 and the discharge flows is 1 m3 /minutes, needed soda ash (Na2CO3) 4,3 kg/hour. Keywords : acid mine drainage, tin , soda ash